ALIH KODE INDONESIA-INGGRIS DALAM LIRIK LAGU “NOW I KNOW” KARYA KALEB J: ANALISIS SOSIOLINGUISTIK - Sofiyatunnida; Nadofah; Dewi Susanti (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2025)
This study examines the phenomenon of Indonesian-English code switching in the lyrics of the song "Now I Know" by Kaleb J. The purpose of the study is to identify the types of code switching and describe their pragmatic functions in building emotional meaning. The method used is descriptive qualitative with a sociolinguistic approach. Data in the form of 36 lines of lyrics are explained using Poplack's typology and Holmes's theory of code switching functions. The results show that intrasentential code switching dominates with expressive and poetic functions. English is used in the chorus to increase the emotional load, while Indonesian is used in the verses to build the narrative. The findings also show that intrasentential code switching dominates at 69.2%, strengthening Poplack's theory about the tendency of bilinguals to use language changes within a clause for efficiency and diagnostics. This study concludes that code switching functions as a musical composition strategy to regulate the emotional intensity of the song.